2021
DOI: 10.1007/s12105-021-01323-7
|View full text |Cite
|
Sign up to set email alerts
|

Papillary and Medullary Thyroid Carcinomas Presenting as Collision Tumors: A Case Series of 21 Cases at a Tertiary Care Cancer Center

Abstract: Collision tumor is the occurrence of two histologically and morphologically distinct tumors within the same organ with no histological admixture. Collision tumors of the thyroid are extremely rare constituting < 1% of all thyroid tumors. Clinical profiles and pathological features of Medullary thyroid carcinoma (MTC) and Papillary thyroid carcinoma (PTC) presenting as Collision tumors of thyroid, diagnosed between 2009 and 2019, at a tertiary care cancer center were retrospectively analyzed. Collision tumors c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
2
19
1
Order By: Relevance
“…A majority of collision tumours identified in previous review by Ryan et al had metastasised at the time of presentation 23. However, a recent case series by Thomas et al have demonstrated disease-free survival in 15 out of 21 (71.4%) of patients with collision tumours, all who have received radical surgery 26. Another case series by Abdullah et al have also demonstrated disease-free survival in six patients who underwent surgical resection 31.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A majority of collision tumours identified in previous review by Ryan et al had metastasised at the time of presentation 23. However, a recent case series by Thomas et al have demonstrated disease-free survival in 15 out of 21 (71.4%) of patients with collision tumours, all who have received radical surgery 26. Another case series by Abdullah et al have also demonstrated disease-free survival in six patients who underwent surgical resection 31.…”
Section: Discussionmentioning
confidence: 97%
“…This case is best categorised as a collision tumour, defined as coexistent but histologically distinct and independent tumours23 and is the first reported collision tumour consisting of HCC and MTC. The most commonly reported thyroid collision tumour combination is that of MTC and papillary thyroid carcinomas 23 26…”
Section: Discussionmentioning
confidence: 99%
“…A collision cancer is the coexistence of two or more tumors of different morphologies within the same location but with no or minimal histological admixture 1,2 . Collision carcinomas have been described in various organs including the cranium, lungs, stomach, larynx, and thyroid gland 3–7 with several cases reported in the head and neck but very rarely in the oral mucosa (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…A collision cancer is the coexistence of two or more tumors of different morphologies within the same location but with no or minimal histological admixture. 1,2 Collision carcinomas have been described in various organs including the cranium, lungs, stomach, larynx, and thyroid gland [3][4][5][6][7] with several cases reported in the head and neck but very rarely in the oral mucosa (Table 1). [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Indeed, and to the best of our knowledge, only two cases of oral collision cancer have been reported (Table 1: Cases 1 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation